Enhanced CO2 reduction activity of polyethylene glycol-modified Au nanoparticles prepared via liquid medium sputtering - Chung, Min Wook; Cha, In Young; Ha, Min Gwan; Na, Youngseung; Hwang, Jungsoo; Ham, Hyung Chul; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Lee, So Young; Park, Hyun S.; et al. (ELSEVIER, 2018)
The electrochemical conversion of CO2 into useful chemicals such as CO is a promising strategy to reduce CO2 emissions from fossil fuel consumption and to mitigate the impacts of global warming. Although tremendous effort has been devoted to the practical use of CO(2)conversion techniques, these techniques still suffer from deficient catalytic activity toward CO2 reduction as well as a complex catalyst synthesis procedure. In this study, an effective strategy to enhance the catalytic CO2 reduction activity with a unique synthesis method is proposed. Polyethylene glycol (PEG)-coated Au nanoparticles supported on a porous carbon support are prepared by a facile, cost-effective, and biocompatible one-step sputtering deposition method, termed liquid medium sputtering. The use of PEG as a liquid medium is advantageous in terms of catalytic activity and stability by producing PEG layers on the Au surface. The prepared PEG-coated Au nanoparticle catalyst exhibits a CO Faradaic efficiency of 100% at 0.57 V and excellent stability during 10 h of operation due to the high solubility of PEG for CO2.